Beginner Teacher's Perception of Application of Project-Based Learning in Mathematics Learning - Guntur, Muhamad Ikhsan Sahal; Retnawati, Heri (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2020)
This research aims to describe the teacher's perception of the application of project-based learning in mathematics learning and how they will apply it using a qualitative case study method. The research subjects in this study amounted to 12 students consisting of 3 men and 9 women, where they were students of post-graduate mathematics education study programs at Yogyakarta State University who were beginner teachers where they had taught between 1 and 3 years. Data collection using interviews with open questions to provoke written perceptions of respondents to the project-based learning approach. The time of the study was carried out starting from December 1, 2018, to January 2, 2019, located at Yogyakarta State University. The data analysis techniques applied in this study are Bogdan, R. C., & Biklen models. The results of this study indicate that: (1) respondents have a good perception of the project-based learning approach, (2) the majority of respondents are interested in using a project-based learning approach after they complete their studies (3) all respondents believe they will find obstacles when applying project-based learning approach later (4) the majority of respondents have less knowledge and experience regarding the project-based learning approach. (5) the need for training and further discussion of the project-based learning approach to the research subjects.